THE FLOUTING MAXIMS OF COOPERATIVE PRINCIPLE ON STEVE’S INTERVIEWS TOWARDS BARACK OBAMA - Wasilah Wasilah; Kartin Lihawa; Usman Pakaya (INJOSEDU: International Journal of Social and Education, 2026)
This study aims to analyze and thoroughly describe the types of conversational maxim flouting carried out by Barack Obama during political interviews, based on Grice's four Cooperative Principle maxims: Quality, Quantity, Relevance, and Manner. The problem examined is how the utterances of a prominent politician disregard these maxims and what the pragmatic function realized through the resulting implicature is. Employing a descriptive qualitative approach, the utterance data were collected from two segments of Obama's interviews with Steve Inskeep on the NPR YouTube channel in June and December 2016. The findings identify a total of 17 utterances that flouted maxims, covering the Maxim of Quality (through statements containing uncertainty), the Maxim of Relevance (by shifting the focus of discussion), the Maxim of Quantity (by providing excessive information), and the Maxim of Manner (by using ambiguous or overly wordy language). This maxim flouting is concluded to be a deliberate pragmatic strategy (implicature) in political communication, utilized to control the public narrative, avoid controversy or criticism, and present complex views, which the implied meaning was proven to be well-understood by the interlocutor.